Dopaminergic receptor blockade changes a functional connectivity network centred on the amygdala. Issue 11 (6th October 2016) - Haaker, Jan; Menz, Mareike M; Fadai, Tahmine; Eippert, Falk; Büchel, Christian
Abstract: Resting‐state connectivity has become an increasingly important measure in characterizing the functional integrity of brain circuits in neuro‐psychiatric conditions. One approach that has recently gained prominence in this regard—and which we use in this study—is to investigate how resting‐state connectivity depends on the integrity of certain neuromodulator systems. Here, we use a pharmacological challenge in combination with functional magnetic resonance imaging to investigate the impact of dopaminergic receptor blockade on whole brain functional connectivity in twenty healthy human subjects. Administration of the D2‐receptor antagonist haloperidol led to a profound change in functional integration in network nodes linked to the amygdala. Compared to placebo and baseline measurements, network‐based statistics and pairwise connectivity analyses revealed reduced connectivity and decreased link strength between the amygdala and the bilateral posterior cingulate cortex and other cortical areas. This was complemented by less extensive but very circumscribed enhanced connectivity between the amygdala and the right putamen during D2‐receptor blockade. It will be interesting to investigate whether these pharmacologically induced shifts in resting‐state connectivity will similarly be evident in clinical conditions that involve a dysfunction of the dopaminergic system. Our findings might also aid in interpreting alterations in more complex states, such as those seen psychiatric conditions and their treatment. Hum Brain Mapp 37:4148–4157, 2016 . ©2016 Wiley Periodicals, Inc.